2022
DOI: 10.3390/su14127235
|View full text |Cite
|
Sign up to set email alerts
|

Do Qualitative and Quantitative Job Insecurity Influence Hotel Employees’ Green Work Outcomes?

Abstract: The extant literature lacks evidence concerning the effects of qualitative and quantitative job insecurity (JIS) on service workers’ performance outcomes. This is also true for their effects on green work outcomes. To fill in this void, drawing on social information processing, threat-rigidity, and the reformulation of attitude theories as well as the model of attitude–behavior relation, this paper proposes and tests a research model that investigates the effects of both qualitative and quantitative JIS simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Second, there are still calls for additional research concerning the psychological mechanism relating JIS to employee outcomes [4,19,25,26]. Therefore, our paper unravels the psychological mechanism through which JIS is associated with proactive PEB.…”
Section: Contributionmentioning
confidence: 90%
See 4 more Smart Citations
“…Second, there are still calls for additional research concerning the psychological mechanism relating JIS to employee outcomes [4,19,25,26]. Therefore, our paper unravels the psychological mechanism through which JIS is associated with proactive PEB.…”
Section: Contributionmentioning
confidence: 90%
“…As a matter of fact, there is limited research about the impact of JIS on performance-related outcomes [10]. Excluding Karatepe's [4] work which reported that JIS impeded hotel employees' green recovery performance and proactive PEBs, past and recent writings do not shed light on whether employees suffering from the threat of job loss in the future do not contribute to the hotel's environmental sustainability efforts through their PEBs [23,24]. Using conservation of resources (COR) theory, we contend that JIS is a stressor that impedes employees' proactive PEBs.…”
Section: Contributionmentioning
confidence: 99%
See 3 more Smart Citations